Effects of methylphenidate on subjective sleep parameters in adults with ADHD: a prospective, non-randomized, non-blinded 6-week trial. (3rd January 2023) - Low, Ann-Marie; Vangkilde, Signe; le Sommer, Julijana; Fagerlund, Birgitte; Glenthøj, Birte; Jepsen, Jens Richardt Møllegaard; Habekost, Thomas
Abstract: Objective: Methylphenidate is a first-line treatment for ADHD; its contribution to sleep problems in adult ADHD is currently unclear. This study investigates (a) subjective sleep disturbances in a group of initially stimulant medication-naïve adults with ADHD and (b) reported changes in sleep problems after 6 weeks of methylphenidate treatment. Method: A prospective, non-randomized, non-blinded, 6-week follow-up study utilising a self-report measure. Results: We found (1) a large difference in reported sleep quality between methylphenidate medication-naïve patients and controls at baseline, (2) a marked improvement in patients after methylphenidate medication, and (3) largest improvement for patients with the poorest reported sleep at baseline. Conclusion: The study indicates that treatment with methylphenidate increases subjective sleep quality for at least some adults with ADHD.